2017
DOI: 10.1016/j.jpeds.2017.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Parental Concern about Environmental Chemical Exposures and Children's Urinary Concentrations of Phthalates and Phenols

Abstract: Objectives To examine whether parents' concerns about environmental chemical exposures were associated with urinary phthalate and phenol concentrations in their school-age children. Study design In a prospective cohort of 218 mother-child pairs from Cincinnati, OH (2010-2014), we measured 11 phthalate metabolites and 5 phenols in urine samples when children were age 8 years and used questionnaire data from caregivers. We estimated the covariate-adjusted percent difference in phthalates and phenols among chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
17
0
3
Order By: Relevance
“…Some studies have evaluated the perceptions, knowledge, and practices regarding the indoor pollution of parents or future parents. In the United States, a study has shown that the more parents are concerned about exposure to environmental chemical compounds, the more their children’s exposure to these compounds is reduced [ 26 ]. In France, most studies have focused on the perceptions [ 27 , 28 , 29 , 30 ] or knowledge [ 27 ] of pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have evaluated the perceptions, knowledge, and practices regarding the indoor pollution of parents or future parents. In the United States, a study has shown that the more parents are concerned about exposure to environmental chemical compounds, the more their children’s exposure to these compounds is reduced [ 26 ]. In France, most studies have focused on the perceptions [ 27 , 28 , 29 , 30 ] or knowledge [ 27 ] of pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested that parents’ perceptions and behavior at home with respect to smoking affected the exposure of their preschool children to air pollution, as demonstrated by altered urine composition [ 19 ]. Hence, parents’ attitudes toward exposure to environmental chemicals can potentially be associated with chemical concentrations in their children’s urine [ 20 ]. On the other hand, some studies have argued that children, through their learning about the environment from school education, can also transmit environmental knowledge and attitudes to their parents, thus affecting their parents’ environmental behaviors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Należy również zwrócić uwagę, iż rodzaj opakowania produktu spożywczego był bardziej istotny dla kobiet aniżeli dla mężczyzn. Badania własne potwierdzają wyniki innych autorów, że rodzice nie są świadomi faktu, iż syntetyczne pojemniki pod wpływem temperatury uwalniają do żywności niebezpieczne toksyny [35,36].…”
Section: Dyskusjaunclassified